Methods For Simplification And Estimation Of Digital Circuit Complexities Using Binary Decision Diagrams - Prasad, P.W. Chandana (2007)
Technological advances in the design and manufacture of integrated circuits have had a tremendous impact on the increase in the complexity of hardware used to build systems. As physical dimensions become smaller, integrated circuits are designed to integrate complex functions; therefore, the complexity of circuit analysis, synthesis and testing also increases.